Design of a Ring National Science Foundation Network (NSFNET) based on Single-Pass and Double-Pass Wavelength Selective Switching (WSS) - هيثم الرضوان; هديل عيسى; أصالة خضور (Latakia University Journal -Engineering Sciences Series, 2023)
Flexible optical networks constitute the fifth generation of optical networks, and interest has increased due to its high flexibility and wide spectrum efficiency. It allowed the spectrum to be divided into a group of frequency slots with a bandwidth of 12.5 GHz, and thus we obtained variable bandwidth and fast access with great efficiency. Flexible optical networks meet the increasing traffic requirements. The main challenge is to determine the resilience of the performance of the individual components and subsystems required to support the networks, so that the design and placement of network elements within the network affects resilience and performance at the network level. In this research, we will be interested in comparing flexibility and selectivity between the single-pass and double-pass of the optical signal within the wavelength selective switch (WSS) based on micro electro mechanical mirrors (MEMS). Finally, we will show the difference between the single and double pass within the switch through a simulation of a ring NSFNET network consisting of 14 nodes based on the switch (WSS) in its infrastructure. So that we studied the performance of the optical paths between the optical nodes that make up the network, the delay time for each optical path, and then measured the input power, the output power, the signal-to-noise ratio, the color dispersion as well as the polarization pattern dispersion at the input and output of each node, and within the optical fibers that connect between the network nodes.